Assessment of fly density, temperature, and humidity in the port areas of the Banyuwangi Regency: Implications for disease vector control - Ali, Khaidar; Hamidya, Syifa Ula; Rizaldi, Muhammad Addin (PT. Mega Science Indonesia, 2025)
Fly density is a critical indicator of environmental sanitation quality and potential risk of disease transmission in port environments. This study assessed fly density levels, temperature, and humidity in port areas of the Banyuwangi Regency to understand vector distribution patterns and inform disease prevention strategies. A quantitative cross-sectional study was conducted at three port locations in Banyuwangi: Ketapang Port, Tanjung Wangi Port (perimeter area), and landing craft machine ports (buffer areas). Fly density was measured via the fly grill method, according to the Indonesian Ministry of Health guidelines. The temperature and humidity measurements were recorded simultaneously at each location. The Kruskal‒Wallis test was used to compare fly density levels between locations. The mean fly densities at waste disposal sites in Ketapang Port, food stalls in Tanjung Wangi Port, and the open dumping area at LCM Port were 9, 9, and 2 flies per block grill, respectively. The average temperatures at the three locations ranged from 29.76°C to 35.53°C, with humidity levels between 62.82% and 77.35%. Statistical analysis revealed significant differences in fly density among the three locations (p<0.05), with the highest mean ranks observed at food stalls in Tanjung Wangi Port. The perimeter areas presented high fly density levels that pose substantial public health risks, whereas the buffer area maintained an acceptable fly density. The environmental conditions recorded at all the sites provided optimal breeding conditions for the disease vectors. The implementation of targeted waste management strategies and environmental sanitation interventions is necessary at perimeter locations to mitigate disease transmission risk and protect public health in these transportation hubs.